A Qualitative Study on Cryptogenic Hepatic Encephalopathy Screening Cognition Among Hepatology Medical Care Personnel - Li XQ; Cao W; Yin TT; Lu R; Li Y; Sha YY (Journal of Multidisciplinary Healthcare)
Xiao-Qin Li, Wen Cao, Tian-Tian Yin, Rui Lu, Yang Li, Ya-Yun Sha Department of Infectious Disease, The Affiliated Taizhou People’s Hospital of Nanjing Medical University, Taizhou, 225300, People’s Republic of ChinaCorrespondence: Yang Li, Department of Infectious Disease, The Affiliated Taizhou People’s Hospital of Nanjing Medical University, No. 399 of South Hailing Road, Hailing District, Taizhou, 225300, People’s Republic of China, Tel +86052386606252, Email liyangll69@126.com Ya-Yun Sha, Department of Infectious Disease, The Affiliated Taizhou People’s Hospital of Nanjing Medical University, No. 399 of South Hailing Road, Hailing District, Taizhou, 225300, People’s Republic of China, Tel +86052386606252, Email shayayuns7@126.comObjective: In this study, we focused on gaining an in-depth understanding on the attitudes and perceptions of hepatology healthcare professionals toward screening for cryptogenic hepatic encephalopathy (CHE), with the goal of providing references for the scientific and standardized implementation of CHE screening.Study Methods: Based on the phenomenological research method, semi-structured in-depth interviews with nine medical professionals were conducted in March 2023 at the department of hepatology of a tertiary hospital in Taizhou city. The collected data was then integrated and analyzed using the Colaizzi seven-step method.Results: Three main themes and seven sub-themes were identified: Inadequate knowledge of relevant information (inadequate knowledge of CHE, inadequate knowledge of neuropsychological test tools for CHE); positive attitudes toward screening for cirrhosis CHE; and screening factors (limited human resources, lack of stringent rules from the management, inability to properly use neuropsychological test tools, lack of cooperation from patients and their families, and lack of auxiliary means of screening).Conclusion: Hepatology medical care personnel had a favorable outlook on CHE screening, however there is room for improvement in both their level of knowledge and clinical work. As a result the administrative departments of hospitals should focus on the factors affecting the clinical work of hepatology medical care personnel and formulate corresponding countermeasures. Emphasis should be placed on the screening and management of CHE for early recognition, early intervention, improvement of quality of life, and effective prevention of hepatic encephalopathy.Keywords: cryptogenic hepatic encephalopathy, cognition, phenomenological research